PENGARUH PENAMBAHAN VANADIUM OKSIDA (V2O5) TERHADAP STRUKTUR KRISTAL Ba 0.9 Ca0.1TiO3 - Rizky N; Suasmoro Suasmoro (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Barium calsium titanate (BCT) is one of perovskite’s crystal structure and has polimorfism to temperature. Composition of BCT was synthesized via oxalate coprecipitation precursor. The powder was V5+ doped by 0; 0.5 and 1 mole %. It was analyzed by thermal analysis. Single phase of BCT was formed at calcination temperature 7000C for 2 hours. The powder was compacted and pelleted. To decrease porous sample sintered at temperature 13000C for 2 hours. Vanadium doped can decrease temperature of sinter to be 12500C. The influences of dopant on samples were analyzed by XRD. Tetragonallity of sample that undoped is 1.0031 and doped V5+ 0.5 % is 1.0026 and doped V5+ 1 % is 1.0019. Characterization on crystal structure show that V5+ subtituted into Ti4+ sites to form single phase of BCT. Keywords: BCT, copresipitation, vanadium, single phase.